Dupilumab efficacy in subgroups of type 2 asthma with high-dose inhaled corticosteroids at baseline. (October 2022) - Bourdin, Arnaud; Virchow, J. Christian; Papi, Alberto; Lugogo, Njira L.; Bardin, Philip; Antila, Martti; Halpin, David M.G.; Daizadeh, Nadia; Djandji, Michel; Ortiz, Benjamin; Jacob-Nara, Juby A.; Gall, Rebecca; et al.
Abstract: Background and objective: Dupilumab blocks the shared receptor component for interleukin (IL)-4/IL-13, key and central drivers of type 2 inflammation in multiple diseases. In phase 3 QUEST (NCT02414854), add-on dupilumab 200 and 300 mg every 2 weeks reduced severe exacerbations, improved pre-bronchodilator forced expiratory volume in 1 s (FEV1 ), and was generally well tolerated in patients with uncontrolled moderate-to-severe asthma. This post hoc analysis assessed dupilumab efficacy in subpopulations of patients with type 2 asthma and high-dose inhaled corticosteroids (ICS). Methods: Adjusted annualized severe exacerbation rates over the treatment period, least squares (LS) mean change from baseline at Week 12 in pre-bronchodilator FEV1, and LS mean change from baseline at Week 24 in 5-item Asthma Control Questionnaire (ACQ-5) scores were analyzed in subgroups of patients receiving high-dose (>500 μg) ICS with baseline blood eosinophils ≥150 cells/μL and/or fractional exhaled nitric oxide ≥25 ppb. Subgroups included allergic phenotype (with/without), comorbid chronic rhinosinusitis and/or nasal polyposis (with/without), pre-bronchodilator FEV1 /forced vital capacity (<70%/≥70%), blood eosinophil level, exacerbation history, median baseline pre-bronchodilator FEV1, age at asthma onset (≤40/>40 years), median FEV1 reversibility, body mass index (<30/≥30 kg/m 2 ), and sex. Results: Dupilumab vs placebo reduced exacerbations and improved pre-bronchodilator FEV1 at Week 12 and ACQ-5 at Week 24 across subgroups of patients with type 2 asthma and high-dose ICS at baseline. Dupilumab was also effective in patients receiving medium-dose ICS. Conclusion: Dupilumab reduced severe exacerbations and improved lung function and asthma control in subgroups of patients with type 2 asthma and high-dose ICS at baseline. Clinical trial registration number: NCT02414854. Graphical abstract: Image 1 Highlights: Dupilumab assessed in patients with type 2 asthma and high-dose ICS at baseline. Patients further divided into subgroups with markers of varying asthma severity. Dupilumab reduced severe exacerbations across subgroups. Dupilumab improved lung function and asthma control across subgroups. Dupilumab demonstrated similar efficacy in patients on medium-dose ICS at baseline.